The Ultimate Traditional Wedding Ceremony:Accommodating Generation Gap of Javanese Familyin Celebrating Nostalgic Moment - Wahyuningtyas, Bhernadetta Pravita; Asteria, Donna; Sunarto, Sunarto (UI Scholars Hub, 2022)
Traditional wedding ceremony legacy helps people to understand their own history, traditions and family better. Marriage is considered as one of the important stages in human life, for a new family will be formed as the next generation in the family. It is also necessary to hold a traditional wedding ceremony since it is the very first beginning to entering the next level of the life cycles for Javanese people. Traditional wedding ceremony is still popular over generations whilst it actually lives and remains amongst the society and becomes valuable cultural experience for the people. People not only celebrate the party but also make the nostalgic moments, which sometimes spark a conflict between generations. This research would describe about how communication contributes its influence in accommodating the generation gap to improve a relationship bonding, especially through the traditional wedding ceremony. In accommodating the generation gap, the communication focuses on the patterns of convergence in communication behaviours. The constructivist paradigm was applied to describe the phenomenon on the Javanese family in absorbing the traditional wedding ceremony as the legacy of the family. The qualitative methods were used to collect data by participant observation and the sampling was purposive sampling. This study found out that that accommodation can resolve the problem between generations and make their interaction as a harmonious interaction. There are surely so many differences amongst generations, such as attitudes, focus, and priorities, the lack of willingness in providing information and doing the voluntary disclosure become another issues in the interaction. However, during the traditional wedding ceremony moments, the communication experiences teaches more than just values and conventions. It also shows moral virtues, generosity, hospitality, love, respect, and the soul of the tradition itself which accommodates the generation gap. Warisan upacara pernikahan tradisional membantu orang dalam memahami sejarah, tradisi, dan keluarga mereka sendiri dengan lebih baik. Pernikahan dianggap sebagai salah satu tahapan penting dalam kehidupan manusia, karena sebuah keluarga baru akan terbentuk sebagai generasi penerus dalam keluarga. Mengadakan upacara pernikahan tradisional juga menjadi penting karena ini adalah awal pertama untuk memasuki tingkat siklus hidup lebih lanjut bagi masyarakat Jawa. Upacara pernikahan tradisional masih ocusa dari generasi ke generasi dan benar-benar dijalani di dalam masyarakat dan menjadi pengalaman budaya yang berharga bagi orang-orang. Orang-orang tidak hanya merayakan pesta tetapi juga membuat momen nostalgia, yang terkadang memicu konflik antar generasi. Penelitian ini akan menjelaskan tentang bagaimana komunikasi memberikan kontribusi pengaruhnya dalam mengakomodasi kesenjangan generasi untuk meningkatkan ikatan hubungan, terutama melalui upacara pernikahan tradisional. Dalam menjembatani kesenjangan generasi, komunikasi berfokus pada pola konvergensi dalam perilaku komunikasi. Paradigma konstruktivis diterapkan untuk menggambarkan fenomena pada keluarga Jawa dalam menyerap upacara pernikahan tradisional sebagai warisan keluarga. Metode kualitatif digunakan untuk mengumpulkan data dengan observasi partisipan dan pengambilan sampel adalah purposive sampling. Penelitian ini menemukan bahwa penjembatan tersebut dapat menyelesaikan masalah antar generasi dan menjadikan interaksi mereka sebagai interaksi yang harmonis. ocusada begitu banyak perbedaan di antara generasi-generasi, seperti sikap, ocus, dan prioritas, kurangnya kemauan dalam memberikan informasi dan melakukan pengungkapan sukarela menjadi masalah lain dalam interaksi. Namun, selama momen upacara pernikahan tradisional, pengalaman komunikasi mengajarkan lebih dari sekadar nilai-nilai dan konvensi. Ini juga menunjukkan kebajikan moral, kemurahan hati, keramahan, cinta, rasa hormat, dan jiwa dari tradisi itu sendiri yang mengakomodasi kesenjangan generasi.